أحكام الشركات بين الشريعة الإسلامية والقانون الوضعي - رحمة قحمية; أية قداش (My University, 2024)
Summary: This research study includes an overview of the various concepts related to the term “company,” as a legal entity that contributes to strengthening the national economy. It dealt with the concept of the company in both Islamic law and positive law, and exposure to the various provisions related to the company in both systems, with the aim of making a comprehensive comparison between the provisions of the company in Islamic law and positive law, to highlight the points of agreement and difference between them, which is what the study concluded, as it showed that there is a similarity between the provisions of the company in Islamic law and its provisions in positive law, and this is clearly evident through the goal of establishing the company and the necessity of having a contract between the partners, There is a joint capital and the responsibility of the partners for the company’s debts. However, this does not prevent the existence of some differences, as they lie in the types of companies in both Islamic law and positive law, the conditions for their establishment, the rights and duties of the partners, and the dissolution of the company. ............................... الملخص: تتضمن هذه الدراسة البحثية الإحاطة بمختلف المفاهيم المتعلقة بمصطلح "الشركة"، ككيان معنوي يسهم في تعزيز الاقتصاد الوطني حيث تناولت مفهوم الشركة في كل من الشريعة الإسلامية والقانون الوضعي، والتعرض لمختلف الأحكام المرتبطة بالشركة في كلا النظامين، وذلك بغرض إجراء مقارنة شاملة بين أحكام الشركة في الشريعة الإسلامية و القانون الوضعي، لإبراز نقاط الاتفاق والاختلاف بينهما، وهو ما خلصت إليه الدراسة، إذ أظهرت أن هناك تشابها بين احكام الشركة في الشريعة الإسلامية وأحكامها في القانون الوضعي، ويتضح ذلك جليا من خلال الهدف من تأسيس الشركة و ضرورة وجود عقد بين الشركاء، ووجود رأس مال مشترك ومسؤولية الشركاء عن ديون الشركة، غير أن ذلك لا يمنع من وجود بعض الاختلافات، حيث تكمن في أنواع الشركات في كل من الشريعة الإسلامية والقانون الوضعي، وشروط تأسيسها وحقوق الشركاء وواجباتهم و حل الشركة. ................................... Résumé: Cette étude de recherche comprend un aperçu des différents concepts liés au terme « entreprise », en tant qu'entité juridique qui contribue au renforcement de l'économie nationale. Elle a traité du concept d'entreprise tant dans le droit islamique que dans le droit positif, ainsi que de l'exposition à la société. diverses dispositions relatives à la société dans les deux systèmes, dans le but de faire une comparaison complète entre les dispositions de la société en droit islamique et en droit positif, pour mettre en évidence les points d'accord et de différence entre elles, ce qui est la conclusion de l'étude, comme il a montré qu'il existe une similitude entre les dispositions de la société en droit islamique et ses dispositions en droit positif, et cela est clairement évident à travers l'objectif de création de la société et la nécessité d'avoir un contrat entre les associés. capital et la responsabilité des associés dans les dettes de la société. Toutefois, cela n'empêche pas l'existence de certaines différences, puisqu'elles résident dans les types de sociétés tant en droit islamique qu'en droit positif, les conditions de leur constitution, les droits et devoirs. des associés et la dissolution de la société.
Keywords: Keywords: company - law - Sharia - contract - partners.; الكلمات المفتاحية : شركة - قانون - شريعة - عقد - شركاء.; Mots clés : société – droit – charia – contrat – partenaires.